Studies On Adsorption/Desorption Of Carbon Dioxide With Respect To Thermal Regeneration Of Hydrotalcites. - Isa, Nadia; W.J., Noel Fernando; Othman, M.R.; Ahmad, A. L. (2008)
This research is focused on evaluation of conditions for thermal regeneration of hydrotalcite. In this study synthesized hydrotalcite prepared under reported optimum conditions namely calcination temperature (600oC) and Mg/Al mol ratio (3.0), and commercial hydrotalcite are compared for adsorption and desorption capacities.